(untitled) (Annals of Bangladesh Agriculture, 2022)
The aloe vera pulp contains more than 98% water and less than 1% total soluble solids (TSS). Blending of pineapple juice and roselle extract with aloe vera may not only increases the TSS level but also add other nutritional properties in the final mixed products. The current study was carried out to investigate the different formulations and the quality of various types of mixed beverages prepared from aloe vera, roselle herb and pineapple juice. Developed products were evaluated for their chemical properties as well as sensory attributes. In addition, selected products were tested for shelf-life potentials. Formulated drinks and juices were found as highly nutritious (maximum of 6.86 mg/100 ml ascorbic acid, 0.045% Ca, 0.26% Mg, 0.154% K, 0.034%Na, and 12.09 ppm Fe). Sensory evaluation revealed that products with 20% and 40% aloe vera pulp with pineapple and roselle extract were highly liked by the consumers. With the storage time, pH and ascorbic acid content decreased (maximum around 40% for pH and around 10% for ascorbic acid respectively) in all the formulated beverages, while TSS increased regardless of the formulations. In addition, aloe vera with pineapple and sugar blend exhibited an acceptable level of microbial load during the shelf-life study. Results from this study suggest that it could be possible to commercially produce aloe vera based value added products, which in turn could play an important role in addressing socioeconomic as well as health conditions. Ann. Bangladesh Agric. (2021) 25 (1) : 43-54